Application of Fast Laser Deprocessing Techniques on large cross-sectional view area sample with FIB-SEM dual beam system. (September 2016) - Zhao, Y.Z.; Wang, Q.J.; Tan, P.K.; Yap, H.H.; Liu, B.H.; Feng, H.; Tan, H.; He, R.; Huang, Y.M.; Wang, D.D.; Zhu, L.; Chen, C.Q.; et al.
Abstract: Cross-sectional analysis is one of the important areas for physical failure analysis. Focus Ion Beam (FIB) and mechanical polish sample preparation are commonly used and necessary techniques in the semiconductor industry and Failure Analysis (FA) Company (Wills and Perungulam, 2007). However, each technique has its own limitation. Mechanical polishing technique easily induces artifact by mechanical force, especially on advance technology node. FIB can eliminate mechanically damaged artifact, but have the limitation on cross-sectional view area. Another potential technique will be plasma FIB, it used very high milling current and fast milling speed (Hrnčíř et al., 2013). However, it comes with a very high cost and having the contamination issue. The contamination issue greatly affects the low kV Scanning Electron Microscopy (SEM) imaging quality. In recent semiconductor industry FA, low kV SEM imaging is preferable, because high kV imaging will introduce delamination artifacts especially on organic material from packaged sample. In this paper, Fast Laser Deprocessing Techniques (FLDT) application is further enhanced on large area cross-sectional FA with fast cycle time and low-cost equipment. This is to prevent from mechanical damage. In short, the proposed FLDT is a cost-effective and quick way to deprocess a sample for defect identification in cross-sectional FA. Highlights: Fast Laser Deprocessing Technique (FLDT) on cross-sectional sample preparation was demonstrated. The technique demonstrated a quick, cost-effective, and a convenient way which improves the efficiency around 70%. An experiment on side effect of FLDT, has proved that only minor damaged ( few micron) on the deprocessed sidewall. FLDT also demonstrated suitability for application on different technology node and package sample.